If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -8 = -53 + 2x Reorder the terms: -8 + -3x = -53 + 2x Solving -8 + -3x = -53 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -8 + -3x + -2x = -53 + 2x + -2x Combine like terms: -3x + -2x = -5x -8 + -5x = -53 + 2x + -2x Combine like terms: 2x + -2x = 0 -8 + -5x = -53 + 0 -8 + -5x = -53 Add '8' to each side of the equation. -8 + 8 + -5x = -53 + 8 Combine like terms: -8 + 8 = 0 0 + -5x = -53 + 8 -5x = -53 + 8 Combine like terms: -53 + 8 = -45 -5x = -45 Divide each side by '-5'. x = 9 Simplifying x = 9
| 18=x+(1.15x) | | -8+5w=-18 | | 2(5x+10)=6x-8 | | 2(y-2)-4y=2 | | 2x^2+3x=70 | | 32q-72=0 | | 3b+7a=-5b-62a | | 10+5c-15=-7 | | u^3-4u-24=0 | | 5+x=3x-5 | | N-7=16-2 | | N-7=16-3 | | 64x^2-80x+25y^2= | | 4+5x=-5x+74 | | 13-6=x | | 3.66X+Y=3 | | (-2.2)-(-6.7)=x | | -4(u+2)=-7u-23 | | c=16+0.40(x-90) | | 7x^2+3x+j=0 | | c=12+0.40(x-90) | | C=8+0.40(x-90) | | 100b^2-81= | | 7-3x=x+3 | | 4(3b-1)=5(2b+3) | | -76+12x=5x+29 | | 5.5x=0.1(4x+10) | | 7-7y=5 | | 9+7x-4x=12 | | ln(x-3)+ln(3x+1)=6forx | | -3x+3(5x-5)=-147 | | 3+2x-3x=10 |